Sistem Kepercayaan dan Peran Perempuan Terhadap Pengelolaan Sumberdaya Hutan di Luwu Timur - Jumardi Lanta; Pawennari Hijjang; Safriadi Safriadi (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
This article aims to (1) describe the local community belief system in preserving the forest so that the forest, (2) analyze the factors that influence the local community to convert forest functions (3) Analyze the role of women in preserving forest resources. The research method is a qualitative method with in-depth interview and observation data collection techniques and use PRA (Participatory Rural Appraisal). The results of the study show that there is a well-preserved community belief system known as